Does the Philippines Need a Trade Representative Office? - Christine Marie Liao; Gloria O. Pasadilla (Philippine Institute for Development Studies (PIDS), 2005)
The paper describes the current decisionmaking structure for trade policy formulation in the Philippines and compares it with the systems in selected countries. It cites difficulties in the current set-up, such as: 1) turf mentality among government agencies that tend to paralyze interagency committees in coming up with an overall position that fully acknowledges trade-offs; 2) lack of appreciation of and capacity for trade research that should inform negotiating positions; 3) unclear delineation of authority; 4) lack of suitable mechanisms for consultation and feedback on negotiation progress and impact, not only regarding tariffs but also of other items under discussion. The paper also stresses the crucial role of trade research in supporting negotiations and suggests ways to strengthen capacity in this area.
Keywords: 330; Philippines; trade institutions; trade capacity building; trade negotiations; Außenwirtschaftspolitik; Handelsliberalisierung; Philippinen